Design and Development of a Bespoke Rotary Friction Welding Machine in Exploration of Joining Dissimilar Materials for Nuclear Applications - Michail Dellepiane; Laurie Da Silva; Athanasios Toumpis (Journal of Manufacturing and Materials Processing)
Rotary friction welding is a solid-state welding process that can manufacture high-integrity joints between similar and dissimilar materials with short weld times. However, access to expensive and complex industrial-grade friction welding machines is not always possible. This study explores the design process and functionality of a laboratory-scale friction welding setup following the fundamentals of large-scale machinery. The proposed setup is designed to be easily manufactured, employing the use of a calibrated drill press and load cell, thus ensuring welding parameters such as rotational speed and applied axial load are monitored. The decision to investigate rotary friction welding of aluminium bronze Ca104 to austenitic stainless steel AISI316 was taken to explore the limitations of this bespoke friction welding machine for prospective applications in the nuclear energy sector. The workpieces were friction welded at four sets of rotational speeds with constant friction and forging pressures. The microstructural evolution and mechanical properties of the dissimilar material welds were investigated via optical and scanning electron microscopy with energy dispersive spectroscopy, 4-point bend testing and microhardness measurements. Results show a change in the hardness along the weld interface and evidence of metallic diffusion between the dissimilar materials, demonstrating the successful application of the small-scale experimental setup.